A Narrative Literature Review Of Digital Library Research As A Source Of Learning During Covid-19 In The Google Scholar Database - Sukma Kurnia Putri; Evi Nursanti Rukmana; Encang Saepudin (Universitas Airlangga, 2022)
The existence of the Covid-19 pandemic requires all people to stop and shift all activities outside the home to be all online, including in the education sector. The distance learning system requires learners to adapt to this new learning pattern. The existence of a digital library helps all the information needs of users during the Covid-19 pandemic through its various services that provide easy access to information needed by the public effectively. The preparation of research is intended to determine the role of digital libraries in supporting learning and providing credible information to the public by analyzing research themes/topics, research methods, and research results. This study applies a narrative literature review type literature study method to five reference sources indexed in Google Scholar with a span of the last ten years. The results showed that digital libraries with various types of services they offer can maintain the quality of information circulating among the public and facilitate access to information so that the teaching and learning process, research and development of science becomes smoother and easier even during the Emergency of the Covid-19 pandemic. Research on digital libraries uses many types of research methods such as qualitative research methods, literature study methods, and Systematic Literature Review (SLR) methods. From the five references analyzed, it can be concluded that digital libraries can be used as a tool to find and obtain learning resources and relevant information during the Covid-19 pandemic. Digital library management requires reliable librarians as parties who distribute all information and knowledge into digital form.